2016
DOI: 10.20471/acc.2016.55.02.12
|View full text |Cite
|
Sign up to set email alerts
|

Dental Fear in Children With Repeated Tooth Injuries

Abstract: SUMMARY -Tooth injuries are serious clinical conditions. Some children experience dental trauma only once, while others are more prone to repeated tooth injuries. Repeated dental trauma occurs in 19.4% to 30% of patients. Pain and dental trauma are the most common reasons for fear and anxiety. Th e main objective of this study was to investigate how dental trauma, as well as repeated dental trauma aff ects the occurrence and development of dental fear in children. Th e study was conducted on a random sample of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…The manner in which children are taught to adapt to stressful situations is determined by the individual’s mental characteristics, their level of intellectual development, and the impact of the environment and other people. This supports the idea that cognitive processes and time factors influence fear perception [ 46 ]. One of the study’s limitations is that the sample was drawn from a single medical institution.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The manner in which children are taught to adapt to stressful situations is determined by the individual’s mental characteristics, their level of intellectual development, and the impact of the environment and other people. This supports the idea that cognitive processes and time factors influence fear perception [ 46 ]. One of the study’s limitations is that the sample was drawn from a single medical institution.…”
Section: Discussionsupporting
confidence: 87%
“…In our study, the proportion of highly anxious children varied from 14.55 to 17.72% regarding the cutoff point (38 or 45), which appears to be a slightly higher proportion than in the general population. However, Negovetić Vranić et al [ 46 ] showed that patients with multiple traumas have a somewhat lower proportion of high anxiety than the general population, potentially due to adaptation to different situations. To our knowledge, this is the first research that attempted to evaluate possible risks such as age, gender, place of residence, child’s sports activity, parents’ knowledge, type of TDI, presence/absence of soft-tissue injury, experiencing pain in the last three months, number of subjective complaints, and oral hygiene status determined via OHI-S in a multifactorial model of dental fear and anxiety (DFA) in children who suffered TDI.…”
Section: Discussionmentioning
confidence: 99%